Rekeying Cultural Scripts for Youth Suicide: How Social Networks Facilitate Suicide Diffusion and Suicide Clusters Following Exposure to Suicide. (July 2020) - Abrutyn, Seth; Mueller, Anna S.; Osborne, Melissa
Research suggests that suicide can socially diffuse through social relationships and social contexts; however, little is known about the mechanisms that facilitate this diffusion. Using data from an in-depth case study of a cohesive community with an enduring youth suicide problem (N = 118), we examine how, after repeated exposure to suicide, the community's cultural script for suicide may have been rekeyed such that suicide became a more imaginable option for some community youth. Essentially, we found evidence that a series of sudden, shocking, suicide deaths of high-status youth may have triggered the formation of new locally generalized meanings for suicide that became available, taken-for-granted social facts. The new meanings reinterpreted broadly shared adolescent experiences (exposure to pressure) as a cause of suicide facilitating youth's ability to imagine suicide as something someone like them could do to escape. We conclude by discussing the implications of our findings for the scientific understanding of (1) suicide and suicide clusters, (2) social diffusion processes, and (3) suicide prevention.